Exposing new compositional coverage of weathered petroleum hydrocarbons through a tiered analytical approach - Bojan, Olivia, author; Blotevogel, Jens, advisor; Sale, Tom, advisor; Denef, Karolien, committee member (Colorado State University. Libraries, 2019)
Petroleum hydrocarbon spills are a widespread source of contamination that may threaten ecosystem services and human health, especially due to modern society's dependence on petroleum-based fuels. Remediation mainly relies on natural source zone depletion (NSZD) processes, which may generate partially oxidized transformation products of the spilled hydrocarbons through weathering or biodegradation processes. These byproducts containing one or more heteroatoms (N, S or O) – referred to as "polar hydrocarbons" – have increased water solubility and mobility in the environment. The unknown fate and toxicity of these complex mixtures of polar metabolites are causing growing concern. The objectives of this thesis were (1) to use a tiered analytical approach to investigate polar transformation products from various sources and (2) to identify common marker compounds that can be used for a more focused characterization of weathering processes at petroleum-contaminated sites. Previous studies have shown that the majority of weathered petroleum hydrocarbon compounds could not be detected by the GC-based analyses currently required by the United States Environmental Protection Agency due to their low volatility and high molecular weight. Therefore, standard methods may yield misleading characterizations of plumes and impede effective risk management. Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS), an emerging analytical technique in the field of "petroleomics" (the characterization of petroleum at the molecular level) offers unrivaled resolving power and mass accuracy; here it was used to determine the elemental composition of highly complex petroleum mixtures present in hydrocarbon-impacted sediment samples collected from field sites with varying redox and hydrogeological conditions. The tiered analysis revealed that GC-based techniques could only detect select nonpolar, low-molecular weight species (<C₃₀) present in the sediment samples, while FT-ICR MS assigned molecular formulas to tens of thousands of individual compounds with a wide range of chemical functionalities. Principal component analyses indicated that species belonging to the O₂, N₁, and HC heteroatom classes – corresponding to carboxylic acids, pyrrolic nitrogen compounds, and PAHs, respectively – may be potential marker compounds for plume characterization. FT-ICR MS results challenged existing site conceptual models and demonstrated the value of this technique as a forensic and source tracking tool. Toxic petroleum-derived N- and S-containing compounds were detected in background samples with "clean" GC chromatograms. Multiple core structures with characteristic double bond equivalents (DBE, a measure of aromaticity) and atomic H:C ratios were associated with unique sources of original spilled products. Asphaltenes, the most recalcitrant fraction of crude oil which is only detectable by FT-ICR MS, were unexpectedly discovered in samples from a former refinery, associating the contaminant plume with a different site owner. Finally, the distribution of polar hydrocarbons between hydrogeologically distinct zones demonstrated the impact of advective transport on the fate of water-soluble metabolites; a higher abundance of oxygenated products was found in an anoxic, low-permeability zone compared to a highly weathered oxic zone of high permeability, challenging previous expectations solely based on redox conditions. This thesis demonstrates the unique capabilities of FT-ICR MS to enable more comprehensive site characterizations than previously possible, consequently exposing many new unknowns about the fate and transport of polar petroleum metabolites. An important limitation of this technique is the semi-quantitative nature of the results due to preferential ionization; relative abundances of the identified elemental formulas do not directly reflect concentration. More research is also needed to inform toxicological studies and risk assessment of these polar metabolite mixtures. Nevertheless, FT-ICR MS can improve understandings of natural attenuation pathways and the long-term fate of the oxidized transformation products at petroleum hydrocarbon-contaminated sites, all in support of better site management.
Keywords: mass spectrometry; petroleomics; FT-ICR MS; petroleum hydrocarbon; natural source zone depletion